Genetics of anther indehiscence with exerted stigmas and its application in hybrid rice breeding. Issue 4 (4th July 2018) - Abebrese, Samuel Oppong; Dartey, Paul Kofi Ayirebi; Akromah, Richard; Gracen, Vernon Edward; Offei, Samuel Kwame; Danquah, Eric Yirenkyi
ABSTRACT: Complete indehiscence of anthers accompanied with exerted stigmas outside the hull could be useful in hybrid rice breeding if the genetics and possible environmental effects are well understood. Studies were undertaken to identify the sources, confirm the mode of inheritance, and examine the possible environmental effects and potential application of anther indehiscence with exerted stigmas in hybrid rice breeding. Direct and reciprocal crosses were made between Jasmine 85, selected interspecific and intersubspecific lines and two wide compatibility varieties. The resulting F1 progenies were evaluated for their expression of anther indehiscence and exerted stigmas. Expression of anther indehiscence with exerted stigmas by both direct and reciprocal crosses suggested no effect of cytoplasmic factors on the expression of the trait. Segregation analysis supported the 7:1 (indehiscence:dehiscence) mode of inheritance. Temperature and relative humidity could not modulate the fertility/sterility status of anther indehiscent plants. Utilization of anther indehiscence with exerted stigmas in hybrid rice breeding was hindered by trait fixation and propagation.